Value Relevance of Accounting Information in the Presence of Earnings Management - Nelwan, Melinda Lydia; Simatupang, Christo; Tansuria, Billy Ivan (Universitas Muhammadiyah Malang)
This study examines the value relevance of accounting information. This study investigates whether accounting information has impact on the share prices. In addition, it examines whether earnings management moderates the value relevance of accounting information to the market. Accounting information in this study consists of earnings, book value of equity, and cash flows, and the earnings management is proxied by discretionary accruals measured using the performance-adjusted modified Jones model. Using time series analysis, there are 98 samples of listed manufacturing corporations used in this study during 2014 which is the period of this study. The results show that earnings, book value of equity, and cash flows simultaneously affect the share prices, meaning that accounting information is value relevant to the market, although there is evidence that partially, only cash flows have impact on share prices. This study also found that the presence of earnings management weakens the value relevance of earnings. To some extent, the results indicate that earnings management eliminates the value relevance of earnings and cash flows.